(untitled) (Research, Society and Development, 2022)
The present work aimed, through analysis with an in silico study, to evaluate the antiviral activity of eucalyptol. The free software PASS Online® was used to carry out the study of the monoterpene eucalyptol, in order to evaluate the pharmacological activity through predictions. In the pharmacological analysis carried out through the in silico study, it was observed that eucalyptol obtained a better result in the activation potential (Pa) compared to the values of probability of inactivation (Pi) for different types of antiviral activity, especially Picornavirus, Adenovirus , Cytomegalovirus – CMV, but also demonstrated several possible biological effects on the human body and is a potent drug candidate with various therapeutic activities, according to the data presented. However, it is worth emphasizing the importance of more details that prove the effectiveness of the molecule through more in vitro and in vivo studies, elucidating with more particularity the mechanism of molecular interaction in a biological environment, revealing the bioactive potential of eucalyptol.